ANALYSIS OF PUBLIC SATISFACTION WITH SERVICES AT SERVICE PLANTING CAPITAL AND SERVICE INTEGRATED ONE DOOR, EAST OKU DISTRICT - Jogie Prasetya; Ibnu Farid; Feni Ira Puspita; Trian Basofi Rohman; Shellya Tanaya Dhayinta (CV. Four Son Scholarship, 2024)
Quality service is quality Which show level Good nor the bad something a type of service from the government to individuals that can provide positive feedback in the form of community satisfaction. This research aims to study the level of public satisfaction with public services at the East OKU Regency Investment and One-Stop Integrated Services Service. This research is descriptive research by conducting a survey of public satisfaction with public services by looking at the Community Satisfaction Index (IKM). The research location is at the Capital Investment Service And Service Integrated One Door Regency OKU East with method distributing questionnaires to public use application google form to 75 respondents. Data were analyzed using the Community Satisfaction Index (IKM) which was calculated using the weighted average value of each service element. In the IKM calculation of the 9 service elements studied, each service element has the same weight. Based on the results of research regarding the Community Satisfaction Index in Service Planting Capital And Service Integrated One Door Regency OKU East In accordance with the provisions of the Minister of State Apparatus Empowerment and Bureaucratic Reform Regulation Number 14 of 2017, each service element is in the good category, this is based on the results of the Community Satisfaction Index value, namely 85.14 in the Good category. It is hoped that in the future, the services provided can be maintained or perhaps can continue to be improved to make them even better.